Kinematics Analysis of 2-CRR/UPU Parallel Mechanism Applied in Apple Manufacturing Line - Zehui Li; Shengtao Song; Haibao Gao; Fengping Ning (Jixie chuandong)
A 2-CRR/UPU parallel mechanism is proposed for apple sorting and packing. A kinematic spiral matrix of 2-CRR/UPU parallel mechanism is established，its degree of freedom is analyzed by the spiral theory，and a modified Kutzbach-Grübler formula is used for verification. Through the geometric relations of the mechanism，the inverse solution of the position of the mechanism is solved，and then the Jacobian matrix of the mechanism is derived and its velocity is analyzed. The workspace of the mechanism is solved by 3D dynamic search method. The singularity of the mechanism is analyzed by Jacobian matrix，and the distribution law of the dexterity index in the workspace is obtained. The 2-CRR/UPU parallel mechanism can carry out three translational motions，and the motion is stable，which can meet the action requirements of apple sorting and packing.